Implementasi Algoritma Travelling Salesman Problem Untuk Pengiriman Paket di PT. POS Indonesia Cabang Surakarta - Kustanto, Kustanto (Jurnal Ilmiah SINUS, 2011)
Travelling salesman problem (TSP) problem is an optimization problem to find the optimal way for the traveling salesman who wants to visit several cities, and returned to the original departure city. TSP is a difficult problem when viewed from the point of computing. Several methods have been used to solve these problems but until now not been found mangkus algorithms to solve them. The easiest way to solve TSP is to try all possible routes and find the optimal route. However, at the time of the very practical now required to complete an algorithm that quickly so that the TSP solution obtained near optimal solutions. TSP is very precise algorithm used for solving complex optimization problems and solved difficult conventional methods. Route and distance data used to determine the optimal route in the system is obtained from the survey results at the post office branch Surakarta City. The results showed that the algorithm is the shortest route from the post office to post office branch Surakarta, The implementation of this system using the programming language PHP, Dreamweaver, MySQL and Fireworks MX. Â  Key words: Â Graph algorithm, Traveling Salesman Problem, optional route